AVALIAÇÃO DO TREINO DE HABILIDADES COMPORTAMENTAIS PARA O ENSINO DE REPERTÓRIOS POR PARTE DE ESTUDANTES DE PEDAGOGIA - GUIMARÃES, Larissa Ferreira (2024)
Autism Spectrum Disorder (ASD) is a developmental disorder that comes with language and communication deficits. Applied Behavior Analysis (ABA) seeks, through interventions, to increase significant skills. A training package called Behavioral Skills Training (BST) might be important to enable academic students and professionals aiming to implement ABA based interventions onto learners with ASD. The present research intended to, in its first experiment, evaluate the BST efficiency surrounding the training of two Pedagogy academic students in the precise teaching of verbal and nonverbal basic skills to a experimentalist (simulating behavior of a ASD child) and for ASD children (during post training generalization investigation). In the second experiment, the same type of investigation was conducted involving two other Pedagogy academic students, but the last two of them were trained in to the precise teaching of skills of retelling stories and answering comprehension questions about the stories. As a result, in both experiments, all the participants showed more accurate performance (behaviors/component of discreet attempts correctly issued) in the teaching of skills to a experimentalist compared to the line base levels. Functional relationship, from the multiple line base non concurrent were displayed between participants. In both investigations, occurred generalization of the precise teaching for real ASD children. All the participants evaluated positively their training, recommending the process to other interested. They all maintained the precise teaching two weeks after the BST training. Limitations were discussed as well as further researches possible recommendations.